Anti-proliferative and cytotoxic activities of the flavonoid isoliquiritigenin in the human neuroblastoma cell line SH-SY5Y. (1st February 2019) - Escobar, Stephane J.de M.; Fong, Genevieve M.; Winnischofer, Sheila M.B.; Simone, Martin; Munoz, Lenka; Dennis, Joanne M.; Rocha, Maria Eliane M.; Witting, Paul K.
Abstract: Neuroblastoma is a common childhood cancer with high mortality. We evaluated the capacity of the flavonoid, isoliquiritigenin (4, 2', 4'-trihydroxychalcone; ISL) to inhibit cellular proliferation and migration in the human neuroblastoma cell line SH-SY5Y. Incubation of cultured SH-SY5Y cells with 20–100 μM ISL decreased cell confluency (15–70%) after 24 h incubation, while 10–100 μM ISL (24 h) depleted intracellular ATP stores (15–90% vs vehicle-treated control) after 24 h incubation. ISL-mediated cell toxicity did not involve intracellular caspase 3/7 activation, externalization of phosphatidylserine on the cell membrane or stimulation of TNF and IL-1β release, all indicating that the flavonoid did not induce apoptosis. Pre-treatment of cells with necrostatin-1, a necroptosis inhibitor, significantly restored ATP levels (ATP levels increased 12–42%) in ISL-treated neuroblastoma cells indicative of enhanced viability. By contrast, RIP1 phosphorylation status remained unchanged in cells treated with ISL although the intracellular ratio of phosphorylated/total parental RIP1 increased after ISL treatment on SH-SY5Y cells indicating that ISL decreased levels of native RIP1. In addition, ISL treatment inhibited SH-SY5Y cell migration/proliferation in a scratch assay and arrested cell cycle transition by significantly decreasing the number of cells in G0/G1 phase and increasing populations by ~10% in S (primarily) and G2/M (lesser extent) phases. The intracellular ratio of phosphorylated/total ERK 1/2 and p38 remained unchanged after ISL treatment (up to 40 μM); ERK activation was only determined at ISL dose well above the experimental IC50 value as judged by ELISA analyses and this did not correlate with ISL cytotoxicity at lower dose <40 μM; Western blot assay confirmed the detection of phosphorylated (p-)ERK1/2 and (p-)p38 in ISL treated cells. Together the results suggest that ISL exerts anti-proliferative and cytotoxic activity on SHSY5Y cells through the loss of ATP, induction of cell cycle arrest, and cell death largely via a necroptotic mechanism in the absence of apoptotic activity. Graphical abstract: Highlights: The flavonoid isoliquiritigenin induces necroptotic death in neuroblastoma cells. The mechanism of cytotoxicity involves decreased ATP, cellular proliferation and cell migration. Isoliquiritigenin may be a natural therapeutic for neuroblastoma. Testing modes of delivery may establish whether therapeutic ISL can be released in vivo.